EFFECTIVENESS LEARNING USING THE GOOGLE CLASSROOM APPLICATION ON UNDERSTANDING OF NURSING STUDENTS ABOUT DISASTER MANAGEMENT - Priyo Mukti Pribadi Winoto; Chilyatiz Zahroh (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Online learning with the help of information and communication technology is very helpful in the current Corona Virus Disease 19 pandemic. Objectives: This study aimed to determine the effect of learning using google classroom on the understanding of the concept of Disaster Management in undergraduate students of Nursing at Nahdlatul Ulama University, Surabaya. Methods: Pre-experimental research design with one group pretest posttest design. The population of all undergraduate nursing study program students and a sample of 30 students by simple random sampling was carried out for 3 months, June-August 2020. Data collection was in the form of a questionnaire about knowledge about disaster management. Statistical test using the Wilcoxon Sign Rank Test. Results: The results of statistical tests obtained a significance value of 0.000 (p value <0.005) which means that there is an effect of using the google classroom method on students' understanding of management. Conclusion: Students' understanding improves after receiving material on hate through google classroom.